Carbon sequistration through oil palm frond biochar for CO2 mitigation and land degradation - Ika Ayu Putri Septyani; Lutfi Fadilah Zamzami (Universitas Trunojoyo Madura, 2025)
The increasing expansion of palm oil plantations can exacerbate climate change due to high deforestation rates and increased CO2 emissions. This study aims to identify carbon sequestration through oil palm frond biochar as a mitigation strategy for CO2 emissions and land degradation. This research conducted at Palm Oil Plantation on Siluman B, Labuhanbatu District. This study using a Factorial Randomized Block Design with two factors, 3 × 2, and 5 replications, resulting in 30 experimental units. The main factor is biochar A0 = No biochar, A1 = 1.5 kg, A2 = 3.0 kg. The second factor is the method of biochar application which includes B0 = Incorporation into soil, B1 = Applied on the soil surface. Biochar significantly increases soil carbon stocks by nearly double, proving its role in carbon sequestration. Application of biochar on the surface and incorporation into soil have the same efect to increase soil carbon sequistration. Biochar fundamentally improves soil fertility by increasing the Cation Exchange Capacity, total N content, and the availability of essential base cations, while lowering the C/N ratio to a more ideal level. The method of incorporating biochar into the soil proved superior for enhancing CEC, making it the recommended practice.